1995
DOI: 10.1007/bf01541853
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer bias in sexuality research

Abstract: Biases associated with volunteering for studies in human sexuality were studied. Beginning with a sample of over 1000 introductory psychology students, subjects participated in a two-phase study in which those willing and unwilling to volunteer for a variety of sexuality studies were compared. In both phases of this study, volunteers were significantly different from nonvolunteers on some, but not all, dimensions assessed. Specifically, compared to nonvolunteers, volunteers reported a more positive attitude to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(142 citation statements)
references
References 10 publications
3
136
0
1
Order By: Relevance
“…For example, because age influences erectile functioning, younger men may be less affected by alcohol than older men (Blanchard & Barbaree, 2005). In addition, volunteers for sexual psychophysiological studies tend to have more sexual experience and liberal sexual attitudes than non-volunteers (Strassberg & Lowe, 1995). Our findings should be interpreted accordingly.…”
Section: Discussionmentioning
confidence: 78%
“…For example, because age influences erectile functioning, younger men may be less affected by alcohol than older men (Blanchard & Barbaree, 2005). In addition, volunteers for sexual psychophysiological studies tend to have more sexual experience and liberal sexual attitudes than non-volunteers (Strassberg & Lowe, 1995). Our findings should be interpreted accordingly.…”
Section: Discussionmentioning
confidence: 78%
“…Men in Study 2 also had to be willing to have their genital arousal measured. Even among participants willing to participate in sexuality research, most are uninterested in participating in studies involving the assessment of their genital responses (Strassberg & Lowe, 1995). Hence, such assessment MALE BISEXUAL AROUSAL AND CURIOSITY 31!…”
Section: Differences Between Studiesmentioning
confidence: 99%
“…However, we acknowledge that even with these efforts, possible self-selection biases remain a concern and may impact the representativeness of the sample and the generalizability of the results. Previous research has shown that volunteers for sexuality-related studies tend to have a more positive attitude towards their own sexuality and more sexual experience than non-volunteers (e.g., see 46,47 ). However, studies have also found that volunteers for sex research are not distinguishable from non-volunteers on most general personality dimensions (e.g., 47 ).…”
mentioning
confidence: 99%
“…Previous research has shown that volunteers for sexuality-related studies tend to have a more positive attitude towards their own sexuality and more sexual experience than non-volunteers (e.g., see 46,47 ). However, studies have also found that volunteers for sex research are not distinguishable from non-volunteers on most general personality dimensions (e.g., 47 ). In order to gain a more reliable picture concerning the generalizability of our findings, replication of the current research is key.…”
mentioning
confidence: 99%